Incidence of Dogbite in Dakshina Kannada, Karnataka: An Epidemiological assessment from 2009 to 2016 - Rao, Ramkrishna; Vittaldas, Rajesh; Dsouza, Jyoshma Preema (Indian Journal of Community Health, 2017)
Background: Animal bites are the main cause of morbidity and death globally. Dog bite cases and rabies are under surveillance under Integrated Disease Surveillance Program in India. Efforts are taken to control dog population and prevent dog bites which are functioning effectively yet needs understanding of the burden of the problem and suitable measures to reduce the burden. Aims and Objective: To understand the incidence dog bite cases from 2009 to 2016 and suggest measures to control the problem. Methods: The cases of dog bite reported to Health facilities in the district were reported to District Surveillance Unit. These cases of dog bite from 2009 to 2016 were included and incidence analysis was done understand the Magnitude of dogbite cases in the District. Results: The article provides an overview of increasing incidence of dogbite cases in Dakshina Kannada from 2009 upto 2016. There is a need to increase effort to control dog population throughout the district and introduce cost-efficient vaccinations. Conclusion: Increasing number of dogs are posing a threat to the community. Majority of the dogs are not supervised, and several are left unvaccinated. The problem needs immediate attention and intersectoral coordination with public involvement